Determination of Tortuosity Using Impedance Spectra Analysis of Symmetric Cell. Issue 11 (3rd June 2017) - Malifarge, Simon; Delobel, Bruno; Delacourt, Charles
Abstract : An approach to increase the autonomy of batteries developed for transportation applications, without changing currently-used positive and negative active materials, is to increase the battery energy density by increasing the active material loading (mg.cm − ²) of the electrodes. A direct consequence of a higher loading is the increase of mass transport-related issues across the electrode porosity. Therefore, the optimization of the porous electrode structure is mandatory to facilitate the access of lithium ions to the whole electrode volume. In this regard, pore tortuosity is a key parameter whose determination is not so straightforward. Although tomography techniques and corresponding analyses are promising methods to acquire precise geometrical information about porous electrode, they hardly can be used as a routine technique. In this work, a transmission-line-model analysis of the electrochemical impedance diagram of symmetric cells containing porous electrodes in blocking condition, i.e. without any charge transfer reaction, is proposed in order to readily derive pore tortuosity. The method is applied to a set of graphite electrodes composed of anisotropic particles.